Stress In Academic Life Of Pharmacy Students: Psychophysiological Assessment Via Cardiovascular Reactivity Experiment - Nori, Ali Yousif (2011)
Research of stress and cardiovascular reactivity (CVR) is one of the pillars in the health care system. It enhances the understanding of human behavior towards daily challenges and needs. It goes further to anticipate precursor risk factors of future cardiovascular disease (CVD). Behavioral or psychological stress is one of many factors that could contribute to the development of essential hypertension (HT) in susceptible individuals. Excessive stress in academic life affects all the students and de-motivates them for gaining higher performance. Specific types of stress are assessed psychologically (by questionnaires), while total affecting stress is assessed physiologically (by the aid of CVR-stress experiments). Two purposes were behind developing the Stress in Academic Life Scale (SALS) in this study: measuring stress, and identifying stressors that interfere with students’ life and their academic achievement. CVR-stress experiment was employed to get clear evaluation of the role of academic stress on the general stress of pharmacy students. For a period of six months, data was collected through participation of a total of 488 students in validation of SALS as well as being part of the physiological CVR-stress experiment.